2010
DOI: 10.4038/sljog.v31i2.1756
|View full text |Cite
|
Sign up to set email alerts
|

Types of urethral catheters for management of short-term voiding problems in hospitalized adults: a short version Cochrane Review

Abstract: Background: Urinary tract infection (UTI) is the most common hospital acquired infection. The major associated cause is indwelling urinary catheters. Currently there are many types of catheters available. A variety of specialized urethral catheters have been designed to reduce the risk of infection. These include antiseptic impregnated catheters and antibiotic impregnated catheters. Other issues that should be considered when choosing a catheter are ease of use, comfort and cost. Objectives:The primary objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…The noble metal alloy indwelling catheter has been shown in multiple large clinical trials and smaller case studies to reduce the incidence of CA-UTI, when compared with conventional catheters. [9][10][11][12][13][14][15] These studies have examined endpoints such as bacteriuria and symptomatic CA-UTI, or surveillance-defined UTI. 8,16,17 In a study by Pickard et al, 17 noble metal alloy catheters were found to be ineffective in reducing the incidence of symptomatic surveillance-defined UTI when used in short-term (mean, 2 days) surgical patients and they did not support the routine use of these catheters in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…The noble metal alloy indwelling catheter has been shown in multiple large clinical trials and smaller case studies to reduce the incidence of CA-UTI, when compared with conventional catheters. [9][10][11][12][13][14][15] These studies have examined endpoints such as bacteriuria and symptomatic CA-UTI, or surveillance-defined UTI. 8,16,17 In a study by Pickard et al, 17 noble metal alloy catheters were found to be ineffective in reducing the incidence of symptomatic surveillance-defined UTI when used in short-term (mean, 2 days) surgical patients and they did not support the routine use of these catheters in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Kateter ilişkili infeksiyonların tümünde temel mekanizma kateter lümeni üzerinde mikroorganizmaların biyofilm tabakası oluşturmasıdır (7)(8)(9) . Üriner kateter takılan hastaların % 20-30'unda ilk 7 gün içerisinde asemptomatik bakteriüri gelişmektedir.…”
Section: Discussionunclassified
“…Silver alloy catheters were found to significantly reduce the incidence of asymptomatic bacteriuria, as reported in a literature review. However, these studies involved <1 week of catheterization (Schumm and Lam, ), so results are inapplicable to long‐term urinary catheterization. Thus, no conclusion has been reached.…”
Section: Introductionmentioning
confidence: 99%